1985
DOI: 10.1002/ana.410180511
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillosis of the central nervous system: Clinicopathological analysis of 17 patients

Abstract: The clinical, laboratory, and pathological features of aspergillosis of the central nervous system (CNS) were studied in a series of 17 autopsied patients. Two groups were defined. Group A consisted of 8 patients with diseases commonly associated with CNS aspergillosis: leukemia, lymphoma, aplastic anemia, and renal transplantation. Group B contained 9 patients with various illnesses not generally known to be associated with CNS aspergillosis. CNS aspergillosis was diagnosed and treated before death in only 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
0
8

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(131 citation statements)
references
References 72 publications
3
120
0
8
Order By: Relevance
“…[38][39][40] In immunocompromised patients aspergillus encephalitis occurs as part of a disseminated infection and invasive aspergillosis is an important cause of death from infection, 41 as confirmed in the present study. We found a mortality of 100% in accordance with former studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[38][39][40] In immunocompromised patients aspergillus encephalitis occurs as part of a disseminated infection and invasive aspergillosis is an important cause of death from infection, 41 as confirmed in the present study. We found a mortality of 100% in accordance with former studies.…”
Section: Discussionsupporting
confidence: 77%
“…We found a mortality of 100% in accordance with former studies. 4,[38][39][40][41] In conclusion, the present study showed toxoplasma encephalitis as the major cause of opportunistic CNS infection after allogeneic BMT. There were two types of toxoplasma encephalitis, which differed in time of onset after BMT, clinical and neuroradiological features and mortality.…”
Section: Discussionmentioning
confidence: 92%
“…The CNS manifestation is usually part of a disseminated infection [4]. Patients are often afebrile or only have a low-grade fever and present with nonspecific neurological symptoms such as stroke-like symptoms or seizures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Positive CSF cultures to Aspergillus are rare. 12 Aspergillus rarely invades the meninges, and the absence of diffuse meningeal involvement might be the reason for relative paucity of CSF findings. 13 Diagnosis of CNS aspergillosis is challenging.…”
Section: Discussionmentioning
confidence: 99%